Komunikasi Krisis Pejabat Publik dan Resepsi Netizen (Viralitas Lagu Bupati Purwakarta 2026) - Sri Riski Wulandari; Muhammad Zia Ulhaq; Rahmat Kurniawan (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Public officials' social media crisis communication often fails to defuse public anger, particularly in crises touching on gender equality, as seen in the viral Sundanese song "Lalaki Langit, Lalanang Bejat" by the Regent of Purwakarta, Saepul Bahri Binzein, which drew national controversy for being seen as demeaning to women. This study analyzes the crisis response strategy the Regent took through his official apology video and maps how netizens received it, extending Situational Crisis Communication Theory with a digital audience reception perspective. Using a qualitative descriptive method with a single case study design, the study gathered primary data through screenshots of the comment section under the official apology video on Instagram @omzein_bupatiaing (7,082 likes, 2,820 comments), after a filtering process, this yielded 30 unique comment units selected purposively based on the highest levels of engagement, which were then analyzed using Situational Crisis Communication Theory to map the crisis response strategy and Stuart Hall's reception theory to map netizen reception. The findings show the Regent's response fell into a diminishment cluster built on a conditional apology and the ‘written before taking office’ defense, which rested on a claim about the timing of authorship prior to holding public office. Of the 30 coded comments, 70% took an oppositional stance, drawing far greater resonance than negotiated or dominant readings, alongside allegations of buzzer activity and the deletion of critical comments that risked deepening the trust crisis. The study concludes that the diminishment strategy and conditional apology model failed to defuse public anger in this morally charged crisis